Answers

2016-03-07T14:29:55+05:30
First of all your equation is not very clear. I assume it to be kx square not 2kx.
We know that if v and u are the two roots of a quadratic equation then,
v + u = -b/a (-coefficient of x /coefficient of x square) and,
vu= c/a (constant term/coefficient of x square)
Here,
v=6u
-b/a= 14/k
So,
7u= -14/k (1)
u=-2k
Also,
vu=6u square
c/a=8/k
6u square= 8k
You can substitute the value of k in respect to u to get a quadratic equation. You can solve that equation to get the answer. You may get two answers. In that case, both the answers are valid.
0